An Alternative to Multiple Protoporphyrinogen Oxidase Inhibitor Applications in No-Till Cotton. (March 2014) - Cahoon, Charles W.; York, Alan C.; Jordan, David L.; Everman, Wesley J.; Seagroves, Richard W.
Abstract : Glyphosate-resistant (GR) Palmer amaranth is a widespread problem in southeastern cotton production areas. Herbicide programs to control this weed in no-till cotton commonly include flumioxazin applied with preplant burndown herbicides approximately 3 wk before planting followed by fomesafen applied PRE and then glufosinate or glyphosate applied POST. Flumioxazin and fomesafen are both protoporphyrinogen oxidase (PPO) inhibitors. Multiple yearly applications of PPO inhibitors in cotton, along with widespread use of PPO inhibitors in rotational crops, raise concerns over possible selection for PPO resistance in Palmer amaranth. An experiment was conducted to determine the potential to substitute diuron for one of the PPO inhibitors in no-till cotton. Palmer amaranth control by diuron and fomesafen applied PRE varied by location, but fomesafen was generally more effective. Control by both herbicides was inadequate when timely rainfall was not received for activation. Palmer amaranth control was more consistent when programs included a preplant residual herbicide. Applied preplant, flumioxazin was more effective than diuron. Programs with diuron preplant followed by fomesafen PRE were as effective as flumioxazin preplant followed by fomesafen only if fomesafen was activated in a timely manner. Programs with flumioxazin preplant followed by diuron PRE were as effective as flumioxazin preplant followed by fomesafen PRE at all locations, regardless of timely activation of the PRE herbicide. As opposed to flumioxazin preplant followed by fomesafen PRE, which exposes Palmer amaranth to two PPO-inhibiting herbicides, one could reduce selection pressure by using flumioxazin preplant followed by diuron PRE without sacrificing Palmer amaranth control or cotton yield.